The Impact of Brand Extension Introduction on Consumer Choice - VANITHA, Swaminathan (Institutional Knowledge at Singapore Management University, 2001)
This article focuses on the impact of a new brand extension introduction on choice in a behavioral context using national household scanner data involving multiple brand extensions. Particularly, the authors investigate the reciprocal impact of trial of successful and unsuccessful brand extensions on parent brand choice. In addition, the authors examine the effects of experience with the parent brand on consumers' trial and repeat of a brand extension using household scanner data on six brand extensions from a national panel. In the case of successful brand extensions, the results show positive reciprocal effects of extension trial on parent brand choice, particularly among prior non-users of the parent brand, and consequently on market share. The authors find evidence for potential negative reciprocal effects of unsuccessful extensions. In addition, the study shows that experience with the parent brand has a significant impact on extension trial, but not on extension repeat.